The effects of social hierarchy and relationships on the emotional expressions used by Bess of Hardwick in her correspondence from c.1550 – 1600s - Viljamaa, Linnea (My University, 2026)
This thesis examines how social hierarchy shaped the emotional expressions used by Bess of Hardwick in her correspondence between c.1550 and 1608. This research investigates how Bess adapted her emotional language when writing to recipients of differing social status, and what these linguistic choices reveal. The primary source of this research is a selection of letters retrieved from the online archive "Bess of Hardwick’s Letters: The Complete Correspondence". The letters were analysed using a custom emotion-coding system combining quantitative tagging of affective lexis with qualitative, context-based interpretation. The coding draws on previous studies on affective language in early modern England and the Historical Thesaurus of the OED, along with theoretical frameworks on emotion, social practice, and early modern letter-writing conventions. The analysis shows clear correlations between recipient status as compared to Bess and the emotional strategies employed. Letters addressed to higher-ranking individuals relied heavily on respectful, formulaic language, with muted emotive language and shaped by humility and deference. Letters to lower-ranking recipients displayed authoritative positioning and minimal affective language. In contrast, correspondence with socially equal recipients contained the richest emotional expression, including affection, concern, and intimate positioning. These findings suggest that emotional language in early modern correspondence was strongly regulated by social hierarchy, with expressive freedom increasing as distance created by social status decreased. The study contributes to historical pragmatics and the linguistic history of emotion by demonstrating how social structures influenced written emotional expression in early modern England.
Keywords: Emotion, letters